Impact of NSCLC metabolic remodeling on immunotherapy effectiveness - Lulu Lv; Ruo han Huang; Jiale Li; Jing Xu; Wen Gao (BMC, 2022)
Abstract It is known that metabolic reprogramming (MR) contributes to tumorigenesis through the activation of processes that support survival of cells, proliferation, and grow in the tumor microenvironment. In order to keep the tumor proliferating at a high rate, metabolic pathways must be upregulated, and tumor metabolism must be adapted to meet this requirement. Additionally, immune cells engage in metabolic remodeling to maintain body and self-health. With the advent of immunotherapy, the fate of individuals suffering from non-small cell lung cancer (NSCLC) has been transformed dramatically. MR may have a profound influence on their prognosis. The aim of this review is to summarize current research advancements in metabolic reprogramming and their impact on immunotherapy in NSCLC. Moreover, we talk about promising approaches targeting and manipulating metabolic pathways to improve cancer immunotherapy's effectiveness in NSCLC.